Efforts to Improve Islamic Values at MI Al-Hidayah Through the Activities of the Kilat Islamic Boarding School - Raden rijianto; Tedi Husaeni; Rizqy Alam Nursamsi; Andriyana; Muhammad Ilham Setiawan; Riyan Inayaturrahman (Indonesian Journal of Society Development, 2024)
Community Service is an application of science and technology to the community through scientific methodology as a noble responsibility of higher education in an effort to develop community capabilities so that they can accelerate the achievement of national development goals. This service is carried out to fill activities in the month of Ramadan, one of which is the express Islamic boarding school at MI Al-Hidayah. With this activity, it is hoped that students will gain Islamic knowledge as a guide in living life in society, nation and state